How Online Learning Evaluation (Kahoot) Affecting Students’ Achievement and Motivation (Case Study on it Students) - Mada, Ratu Dea; Anharudin, Anharudin (Universitas Malikussaleh, 2019)
It is undeniable that the development of technology in the present impacts on various aspects, especially in the field of learning technology. In learning, lecturers are required to implement innovations in the field of technology. One of the implementations of education technology is the implementation of evaluation by using Kahoot. Kahoot is a game-based learning platform. By implementing this learning evaluation, we expect students' achievement and motivation in learning to improve. The research method of this research is simple qualitative descriptive using a questionnaire that were distributed to the first semester Informatics Engineering students as the object of this research. From the questionnaire the results showed that 82.2% of students stated that Kahoot was able to increase their learning motivation. Other results is the increasing of students’ scores in this evaluations and the obstacle found in implementing this evaluation is the umstable connections or internet networks.